PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PASIEN RUMAH SAKIT UMUM DAERAH (RSUD) DI KABUPATEN BOYOLALI PROVINSI JAWA TENGAH - -, Suwardi (Transformasi, 2012)
Abstrak Quality of inpatient care government hospitals (RSUD) variable constructed tangible, reliability, responsiveness, assurance, empathy, and equity. The sixth variable effect on satisfaction. However, not all variable effect on loyalty. Empathy and equity has no effect on loyalty. The study also concluded that no significant satisfaction to loyalty Â  Keyword : Service Quality; Satisfaction; And Loyality.